A STUDY OF FACTORS AFFECTING RESEARCH COMMITMENT AMONG POSTGRADUATE STUDENTS - Eze, Hyacinth O. (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
The university's post-graduate research activities are an essential part of the educational curriculum geared toward scientific research development in academia. Past research has underscored numerous constraints in post-graduate research. However, little is known about the effects of the supervisor's factor and computer acceptance on the commitment to research. The paper examined post-graduate research commitment based on perceived supervisor's research competence and computer self-efficacy. Ninety-six students enrolled in graduate programs in public universities in the Enugu and Ebonyi States of Nigeria participated in the study. Data were collected using self-report measures. The present study's purpose was to understand better the predictive roles of perceived supervisor's research competence and computer self-efficacy on post-graduate students' research commitment. The result supports the hypothesis that the main independent variables of the study statistically significantly predicted research commitment, F (2, 94) = 31.205, p < 0.05. All two variables contributed significantly to the prediction, p < .05. The result revealed that the predictor variables contributed 14.1% of the variance in the post-graduate research commitment. The result has implications for research development in academia.